ONION HARVESTER CONVERYOR - P. T. Wandhekar; S. D. Pataskar; P. M. Bande; H. B. Pawar (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Onion harvesting machine is based on reduction in effort required for harvesting of onion as well as for saving cost required in harvesting, specially for small scale farming. Our purpose of designing and fabrication of such small equipment is that it fulfills requirements of harvesting and reduces the cost of it. The main aim of the study is to determine optimum design and operational parameters of tractor drawn onion harvester. The tractor drawn onion harvester has two main working units e.g. digging unit and separating unit consisting of conveyer. The machine intends to lift the lodged crop, dig the bulbs, lift the dug bulbs and finally windrow the crop after separating the soil. Onion harvesting machine contains simple mechanisms with effective reduce need only human efforts for operations. The purpose behind this project is to develop a system which can easily attach to any tractor (more than 40 HP). Due to use of this mechanism we can reduce harvesting cost of onion and the farmer can get more output & income specially considering small scale farming.